2015
DOI: 10.1002/ejp.657
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2 is required for the modulation of spinal nociceptive information related to ephrinB/EphB signalling

Abstract: These results confirmed the important involvement of COX-2 in the modulation of spinal nociceptive information related to ephrinBs-EphBs signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Intrathecally injected ephrinB activates their EphB receptors and produces long-lasting MWT and TWL ( 23 , 24 ). However, which subtype mainly mediating nociceptive pain remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Intrathecally injected ephrinB activates their EphB receptors and produces long-lasting MWT and TWL ( 23 , 24 ). However, which subtype mainly mediating nociceptive pain remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the treatment that inhibited this interleukin was shown to attenuate allodynia and hyperalgesia [36]. However, it induces a variety of diseases through overproduction [37].…”
Section: Inflammatory Cytokines Levels In the Supernatant Of The Raw ...mentioning
confidence: 96%
“…Compared to the control induced with LPS only, significant reductions in IL-1β, IL-6, and IL-12 expressions were found in the cells treated with quercetin and WOEE (Figure 5a-c) in a dose-dependent manner. In a previous study, it was reported that quercetin inhibited the secretion of LPS-activated IL-1β, IL-6, and TNF-α proteins in the culture medium [37]. Inflammatory cytokines are a type of glycoprotein released from cells that are used for signaling for immune responses.…”
Section: Inflammatory Cytokines Levels In the Supernatant Of The Raw ...mentioning
confidence: 99%
“…Given the important roles of eph-rinB-EphB signaling in the generation and maintenance of chronic pain, researchers have always focused on exploring the upstream and downstream signal pathway (11,12) have demonstrated that some MAPKs such as ERK1/2, p38, and JNK, are involved in the ephrinB-EphB signaling-induced hyperalgesia. Our previous studies have consecutively proved that phosphatidy linositol 3-kinase (PI3K), protein kinase A (PKA), and protein kinase Cγ (PKCγ) act as the downstream factors of ephrinB-EphB signaling in modulating the spinal nociceptive information (7,(43)(44)(45). In the present study, we hypothesized that ERK5/CREB pathway may act as the downstream signal pathway of ephrinB-EphB signaling in modulating pain transduction.…”
Section: Discussionmentioning
confidence: 80%